2002
DOI: 10.1111/1468-0297.0j677
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Hazard in a Power‐to‐Take Experiment

Abstract: In this experimental study of a two player power-to-take game, players earn an income in an individual effort task preceding the game. The game has two stages. First, one player can claim any part of the other's income (take rate). Then, the latter player can respond by destroying own income. We focus on how emotions in¯uence responses and show: (1) a higher take rate increases (decreases) intensity of negative (positive) emotions; (2) negative emotions drive destruction; (3) at high emotional intensity, respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
263
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(284 citation statements)
references
References 39 publications
17
263
0
4
Order By: Relevance
“…punishment in our experiment, are. Recent research has identified emotions as one possible source (Bosman & Van Winden 2002;Sanfey et al 2003;de Quervain et al 2004; S. Gächter, personal communication, but see also Knoch et al (2006) who challenge this view) and our results are consistent with such an interpretation. However, the strong response in punishment behaviour to our variations in the cost and the impact of punishment indicate that the decision to altruistically punish is also strongly influenced by material economic incentives.…”
Section: Discussionsupporting
confidence: 90%
“…punishment in our experiment, are. Recent research has identified emotions as one possible source (Bosman & Van Winden 2002;Sanfey et al 2003;de Quervain et al 2004; S. Gächter, personal communication, but see also Knoch et al (2006) who challenge this view) and our results are consistent with such an interpretation. However, the strong response in punishment behaviour to our variations in the cost and the impact of punishment indicate that the decision to altruistically punish is also strongly influenced by material economic incentives.…”
Section: Discussionsupporting
confidence: 90%
“…For each correct assessment they receive 50 cents. Finally, subjects state their emotions on a seven-point scale using the same types of emotions as Bosman and Van Winden (2002). 7 Although, I am mainly interested in anger, happiness, and surprise (see also Bolle, Tan and Zizzo, 2014), I include all types of emotions as filler questions and so as to avoid leading subjects in a specific emotional direction.…”
Section: Methodsmentioning
confidence: 99%
“…It is also apparent that framing of the game can a¤ect what players perceive as fair shares. For example, in the power-to-take game (Bosman and van Winden, 2002) players rep-540 resenting tax authority tend to claim substantial amounts, thus opting for an allocation far from equality, apparently exhibiting more greediness than they would in the ultimatum game. A relatively simple 11 extension of my model that would admit capturing such regularities is a modi…cation of the assumption regarding reference point, e.g.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…These games are similar to the ultimatum game in that in both of them the …rst party has an opportunity to sacri…ce for the bene…t of the 285 other player, who can subsequently respond with "reward" or punishment. While I do not provide detailed analysis of these games (which have richer strategy spaces than ultimatum game), 8 a short re ‡ection shows that the logic underlying Statement 9 applies also here.…”
mentioning
confidence: 99%